Crack path simulation for cylindrical contact under fretting conditions (Fracture and Structural Integrity, 2015)
In this work different strategies to estimate crack path for cylindrical contacts under fretting conditions are carried out. The main goal is to propose and to evaluate methodologies not only to estimate the direction of crack initiation but also the subsequent propagation in its earlier stages, where the stress field is multiaxial, non-proportional and decays very fast due to the proximity with the contact interface. Such complex conditions pose a substantial challenge to the modelling of crack path. The numerical simulations are provided by a 2D Finite Element Analysis taking into account interactions between the crack faces. The results show that, under fretting conditions, models based on the critical plane method are not effective to estimate the crack initiation orientation, while models based on a so called “critical direction” applied along a critical distance provide better results. Regarding the subsequent crack propagation orientation, it was possible to see that stress intensity factor based models where one considers an infinitesimal virtual crack emerging from an original preexistent crack are powerful mechanisms of crack orientation estimation
Keywords: Fretting fatigue; Crack propagation; Critical distances